The origin of personal non-property rights of minor citizens - E.M. Podrabinok (Ученые записки Казанского университета: Серия Гуманитарные науки)
The emergence of personal non-property rights of minor citizens was analyzed. It was revealed that personal non-property rights that ensure physical existence (such as the right to life, health, favorable environment, etc.) and social well-being (for preserving personal identity and freedom, such as the right to honor, dignity, good name, etc.) arise from the moment of birth. The author’s personal non-property rights (for instance, the right of authorship, copyright, as well as the right to disclosure, revision, and integrity) arise for a minor citizen from the moment they achieve the result of an intellectual activity, regardless of whether they are aware of it or not and the “quality” of the result.